(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
“Baburnama” is the masterpiece of Zahiriddin Muhammad Babur. Scientists have found that 28,000 words are used in this work, and it attracts the attention of many researchers. Although many scientists have worked on this work, there are still some unexplored issues. This can be an example of a thesaurus, which is one of the current problems in the field of linguistics. In this article, some of these words are explained scientifically as a thesaurus. In the process of creating a thesaurus of the work, we can success many new scientific achievements in computer linguistics.